Pathogenesis of psoriasis in the “omic” era. Part I. Epidemiology, clinical manifestation, immunological and neuroendocrine disturbances - Samotij, Dominik; Nedoszytko, Bogusław; Bartosińska, Joanna; Batycka-Baran, Aleksandra; Czajkowski, Rafał; Dobrucki, Iwona; Dobrucki, Lawrence; Górecka-Sokołowska, Magdalena; Janaszak-Jasienicka, Anna; Krasowska, Dorota; Kalinowski, Leszek; Macieja-Stawczyk, Marta; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Psoriasis is a common, chronic, inflammatory, immune-mediated skin disease affecting about 2% of the world’s population. According to current knowledge, psoriasis is a complex disease that involves various genes and environmental factors, such as stress, injuries, infections and certain medications. The chronic inflammation of psoriasis lesions develops upon epidermal infiltration, activation, and expansion of type 1 and type 17 Th cells. Despite the enormous progress in understanding the mechanisms that cause psoriasis, the target cells and antigens that drive pathogenic T cell responses in psoriatic lesions are still unproven and the autoimmune basis of psoriasis still remains hypothetical. However, since the identification of the Th17 cell subset, the IL-23/Th17 immune axis has been considered a key driver of psoriatic inflammation, which has led to the development of biologic agents that target crucial elements of this pathway. Here we present the current understanding of various aspects in psoriasis pathogenesis.